Cultural Guidelines for Commercial Production of Interiorscape Philodendron - Dennis B. McConnell; Jianjun Chen; Richard J. Henny; Kelly C. Everitt (EDIS)
This article describes common Philodendron species and cultivars in the foliage plant industry, provides guidelines on their culture and interior use, and lists physiological problems encountered in both production and in the interiorscape. This document is ENH893, a series of the Environmental Horticulture Department, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: April 2003.